STRUCTURAL AND OPTICAL PROPERTIES OF CdTe THIN FILMS SYNTHESIZED BY LASER ABLATION ON SODA LIME GLASS SUBSTRATE - Mahmood, N.; Ilyas, Bushra; J. Akhtar, S. M.; Khan, M. N.; Bashir, J. (The Nucleus, 2011)
Cadmium Telluride thin films with thicknesses 46 nm were deposited on soda lime glass substrates at room temperature by pulsed laser ablation technique. These films were then annealed in air at different temperatures. X-ray diffraction measurements showed that the as grown films are amorphous transforming to crystalline structure with annealing. Crystalline films with good quality were obtained when annealed at 200 - 300 o C. The results are in confirmation to the optical and atomic force microscopic studies on these films. The crystalline films possess cubic zinc blende structure. The growth occurred preferentially in the (111) direction. Annealing at higher temperatures >300 o C revealed that, the films reacts with glass substrate resulting in the deterioration of films crystallinity. The crystalline film showed a transmission of more than 80%. The optical parameters determined by the ellipsometry measurements showed values in close proximity to the bulk CdTe demonstrating its potential for photovoltaic device application.